# Solve for y -3(y-5)+9y=3y-8

-3(y-5)+9y=3y-8
Simplify -3(y-5)+9y.
Simplify each term.
Apply the distributive property.
-3y-3⋅-5+9y=3y-8
Multiply -3 by -5.
-3y+15+9y=3y-8
-3y+15+9y=3y-8
Add -3y and 9y.
6y+15=3y-8
6y+15=3y-8
Move all terms containing y to the left side of the equation.
Subtract 3y from both sides of the equation.
6y+15-3y=-8
Subtract 3y from 6y.
3y+15=-8
3y+15=-8
Move all terms not containing y to the right side of the equation.
Subtract 15 from both sides of the equation.
3y=-8-15
Subtract 15 from -8.
3y=-23
3y=-23
Divide each term by 3 and simplify.
Divide each term in 3y=-23 by 3.
3y3=-233
Cancel the common factor of 3.
Cancel the common factor.
3y3=-233
Divide y by 1.
y=-233
y=-233
Move the negative in front of the fraction.
y=-233
y=-233
The result can be shown in multiple forms.
Exact Form:
y=-233
Decimal Form:
y=-7.6‾
Mixed Number Form:
y=-723
Solve for y -3(y-5)+9y=3y-8

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top